Loc108167440 suppressed myeloma cell growth by P53-mediated apoptosis. Issue 10 (24th August 2019) - Zhai, Bing; Hou, Chunmei; Xu, Ruonan; Fang, Ying; Xiao, He; Chen, Guojiang; Wang, Xiaoqian; Ma, Ning; Han, Gencheng; Wang, Renxi
Abstract: Multiple myeloma (MM) results from biased proliferation of cancerous plasma cells (PC). Therapeutic strategies that target MM PC will provide immense value to the treatment of MM. For this, it is necessary to identify novel molecules that differ between MM PC and healthy PC. RNA sequencing was used to determine differences in gene expression profiles between LPS-induced plasmablasts (PB)/PC and the PB-like myeloma SP 2/0 cell line. Compared to LPS-induced PB/PC, SP 2/0 cells expressed significantly lower levels of Loc108167440 mRNA. Loc108167440 overexpression reduced the number of SP 2/0 cells by stimulating apoptotic cell death. In addition, Loc108167440 overexpression suppressed tumor progression in the SP 2/0 xenograft mouse model. Finally, we demonstrated that Loc108167440 overexpression up-regulated expression of p53 in SP 2/0 cells. These results suggest that Loc108167440 overexpression suppressed SP 2/0 cell growth by inducing p53-mediated apoptosis. Thus, Loc108167440 overexpression may be a potential therapy for treating MM.